The Relationship between Body Mass Index (BMI) and Gestational Diabetes Mellitus (GDM) - Muarrofah; Rahmawati, Anita; Afifah, Nur Asiyah (Babali Nursing Research, 2025)
Background: Gestational Diabetes Mellitus (GDM) is a growing metabolic complication in pregnancy, affecting 1 in 6 births globally. In Indonesia, obesity prevalence among women of reproductive age reached 26.7% in 2022, with local studies in East Java reporting GDM rates as high as 27.4%. Methods: This cross-sectional study involved 42 pregnant women at Puskesmas Jelakombo, Jombang , in December 2024. Participants were selected using purposive sampling based on gestational age ≥24 weeks and complete OGTT results. The study used weight and height measurements to calculate Body Mass Index (BMI) and Oral Glucose Tolerance Test (OGTT) results to diagnose Gestational Diabetes Mellitus (GDM). These tools helped determine if there is a link between BMI and GDM risk in pregnant women. BMI was categorized using WHO standards , and GDM was diagnosed using the 2013 WHO OGTT criteria . Data were analyzed using the chi-square test. Results: Of the participants, 57.1% were diagnosed with GDM. Among them, 45.2% were overweight and 11.9% were obese. Statistical analysis showed a significant association between BMI and GDM risk: p = 0.00052; OR = 8.6; 95% CI: 2.4–30.8. Conclusion: Higher BMI is strongly linked to increased GDM risk. This highlights the importance of routine BMI screening and nutritional counseling during antenatal care, especially in primary healthcare settings with limited access to specialized services.